Evaluation of the Unslotted CSMA_CA in Zigbee Networks - KHOUNI, Sadika; KHESRANI, Samia (International Conference on Applied Engineering and Natural Sciences, 2023)
A Zigbee network with 12 nodes (end device) and a coordinator is developed to evaluate the performance of the un-slotted CSMA_CA protocol for the two frequency bands 2.4GHz and 900 MHz by varying the BE (Backoff Exponent) parameter . The simulation is effected for BE=1, 2 and 3 to observe the End to End delay which characterizes the response speed of the network. The network implementation and his simulation were effected under Opnet 14.5.